Lack of effects of glyphosate and glufosinate on growth, mineral content, and yield of glyphosate- and glufosinate-resistant maize - Costa F.R.* (2018)
© 2018, © 2018 Taylor & Francis.Whether herbicides used in transgenic, herbicide-resistant crops have negative effects on those crops has been controversial. Most all of the data on this topic has been on glyphosate-resistant (GR) soybean, with little information available on GR and glufosinate-resistant (GluR) maize. A GR plus GluR maize variety was evaluated in the greenhouse and the field for effects of glyphosate and glufosinate on growth, mineral content, and yield. Treatments were: 1) a herbicide-free control; 2) 980 g acid equivalent (a.e.) ha−1 glyphosate at 21 days after emergence (DAE); 3) 600 g active ingredient (a.i.) ha−1 glufosinate at 21 DAE; 4) sequential applications of glyphosate at 520 and 980 g a.e. ha−1 at 14 and 28 DAE, respectively; 5) sequential applications of glufosinate at 300 and 300 g a.i. ha−1 at 14 and 28 DAE, respectively; and 6) sequential application of glyphosate (980 g a.e. ha−1) and glufosinate (600 g a.i. ha−1) at 14 and 28 DAE, respectively. None of the herbicide treatments affected plant growth, yield, or content of N, P, K, Ca, Mg, S, Mn, Fe, Cu, or Zn in the greenhouse or field. In grain of field-grown plants, no glufosinate was found and glyphosate (0.12 ng g−1) was only found in the sequential glyphosate treatment.